Kaiwa Learning Using Role Play Method On Students Of The Faculty Of Health Science Assyafiyah University In Improving Japanese Speaking Skills - Alo Karyati; Yelni Rahmawati (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
The aims of this research to see the effectiveness of the role play method in improving Japanese speaking skills in students of the Faculty of Health Sciences, Assyafiiyah Islamic University. Speaking ability is very important in teaching Kaiwa / Japanese Conversation. Speaking is a medium of communication to convey ideas, intentions, and messages to others. Through speaking we can convey ideas and intentions to the other person. The formulation of the problem in this research are: (1) Can the role play method using role cards improve speaking skills? (2) How is the speaking ability of the students of the Faculty of Health Sciences, Assyafiiyah Islamic University before and after using the role play method? (3) Are there any differences in speaking ability before and after using the role play method? (4) What are the obstacles faced by students when learning Kaiwa using the role play method with role cards? The research method used in this paper is true experimental. In this research, the researcher did not conduct class control, the research only focused on 1 class. Treatment was carried out for 5 times. The population of this research were students of the Faculty of Health Sciences, Assyafiiyah Islamic University with a sample of 20 students. The data analysis technique uses the SPSS application. The data to be analyzed is the value of pretest, posttest and also a questionnaire from google form. The results of this research are expected to be useful for Kaiwa teachers in general, and especially for students who are studying Japanese.